Human Animal - Lasaga Medina, José (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2013)
This article discusses the difference between the human and the animal in the philosophy of Ortega y Gasset, relating the difference with some of the central issues as the role of art in human life and its role in the articulation of its two dimension constituents, nature and history. In short, we reflect on the role of the animal to clarify the meaning of the adjective "human" in the philosopheme "human life", decisive in Ortega's metaphysics, and in one can speak of a new "humanism" not founded on supposed superiority of the "rational animal".